A new species Begonia wiformis, and a new record of B. filiformis (B. sect. Coelocentrum, Begoniaceae) from nothern Vietnam - Hoang, Thanh Son; Lin, Che-Wei (Phytotaxa, 2023)
Begonia sect. Coelocentrum is a highly diverse section of the genus (87 species) with a Sino-Vietnamese distribution. A new species, Begonia wiformis, is described and illustrated herein, it is characterized by its rhizomes that send out elongated stolons, subglabrous lamina with a velvety texture adaxially, bracts with a denticulate margin, and a zygomorphic androecium. Additionally, Begonia filiformis, a species previously known only from China, is reported for the first time in Vietnam.